Pedagogical Experience of Classroom Teachers in English as a Medium of Instruction - Shrestha, Suresh Kumar (Studies in ELT and Applied Linguistics, 2021)
English as a medium of instruction (EMI), especially at public schools, is a matter of curiosity and exploration among Nepalese academicians and researchers, as it is already in policy and practice with the growing number of public schools implementing it. Therefore, it is essential to explore the perceptions and experiences of all the stakeholders in Nepal to address the issues of EMI in the local context. The article outlines teachers’ experiences of EMI in classes in the Nepalese multilingual context. It builds upon the experiences of three teachers teaching several subjects including English at private and public EMI schools. The semi-structured written interviews were employed to collect required data. The teachers’ experiences have been presented in four aspects: teaching techniques, achievements, challenges and strategies disclose the hopes and challenges both the teachers and students including parents and school administration experience. The findings hint the imperativeness of discussions at different levels from locals to policy makers for the proper understanding and management of EMI at schools.